CS-12 Outcomes of lupus nephritis in vulnerable populations. (August 2018) - Peschken, Christine; Gole, Rebecca; Hitchon, Carol A; Robinson, David; Man, Ada; Tisseverasinghe, Annaliese; El-Gabalawy, Hani
Abstract : Background: Lupus nephritis is a known predictor of mortality; we examined the risks of end-stage renal disease (ESRD) and death among lupus nephritis patients, and included the impact of ethnicity, low income (LowInc), lack of education (LowEduc), and living >500 km from rheumatology care (Remote). Methods: Patients from a single academic center were followed from 1990–2016 using a custom database. Records of all SLE patients were abstracted. Variables included birthdate, diagnosis date, ethnicity, ACR classification criteria (ACRc), SLICC Damage Index (SDI) including ESRD, treatment and date of death. Ethnicity was categorized into North American Indigenous (IND), Asian (ASN), Caucasian (CAU), and Other. In patients who had developed nephritis, Kaplan Meier and Cox proportional hazard models were used to compare ESRD and survival between vulnerable groups. Results: Nine hundred forty-four SLE patients were identified: 240 (25%) IND, 576(60%) CAU, 104(11%) ASN and 24(2.5%) Other. 'Other' patients were excluded from further analysis. Mean disease duration was 14 years, 89% female. Nephritis developed in 39% of CAU (n=224), 57% of IND (n=136; OR 2.1; 95% CI 1.5 to 2.8), and 75% of ASN (n=76; OR 4.7; 95% CI 2.9 to 7.6), p<0.001. Twenty percent of patients had not completed high school, 20% were LowInc, and 11% were Remote; LowInc, LowEduc, and Remote did not increase the odds of nephritis. Among nephritis patients, ESRD developed in 11% and 17% died. Risk of ESRD was increased in IND (HR 4.2; 95% CI 2.0 to 8.6) and ASN (HR 5.8; 95% CI 2.6 to 12.6) compared to CAU (figure 1a). Risk of death was increased in IND (HR 2.6; 95% CI 1.6 to 4.2), but not in ASN (HR 1.1; 95% CI 0.5 to 2.4) compared to CAU (figure 1b). In separate cox proportional hazards models, after adjustment for age, gender, SDI, ACRc, and age at diagnosis, risk of ESRD was increased in NAI (HR 2.8; 95% CI 1.0 to 8.1) and ASN (HR 4.0; 95% CI 1.6 to 10.3) compared to CAU. LowInc, LowEduc, and Remote did not increase risk of ESRD. Only LowEduc (HR 2.1; 95% CI 1.1 to 3.9) increased the adjusted risk of death; ethnicity, LowInc and Remote were not significant. Conclusions: Compared to CAU, IND and ASN not only have a higher risk of nephritis, but among those with nephritis, risk of ESRD is 3–4 fold higher in IND and ASN. Lack of education, rather than ethnicity, was the major risk factor for death. Reasons for these differences may include renal pathology, care pathways, comorbid conditions and additional socioeconomic factors and need to be further explored. Acknowledgements: We gratefully acknowledge the Lupus Society of Manitoba for ongoing funding for this work.